IPTEKS PERLAKUAN AKUNTANSI OPERATING LEASE DI DEALER HINO MANADO - Wowor, Brigita Carmelia; Rondonuwu, Sintje (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
Nowadays, it cannot be denied that a large level of innovation in the automotive business sector has opened up so many opportunities to develop ourselves, express creativity, and put ideas into the business world. This was seen by Dealer HINO Manado as a good business opportunity to develop the company's revenue sources, in the form of fixed asset leases. However, to optimize profitability through this type of business, the accounting treatment for leases must also be carried out in accordance with applicable standards. In this case, the Dealer HINO Manado rents out fixed assets using the operating lease as the basis for accounting treatment. This study aims to find out how the accounting treatment for operating leases is applied at the Dealer HINO Manado. The Ipteks method used is the application of the operating lease accounting treatment by taking into account the recording criteria in accordance with the applicable accounting standards, namely recording assets, using the method of calculating prices, accumulating depreciation and recognizing gains and losses.